Effect of low intensity pulse ultrasound on the neutrophil function and epithelial thickness after skin excision in diabetes mellitus type 2 rats’ model (an immunohistochemistry study on matrix metalloproteinase-9) - Titis Laraswati; Cahya Y. Hasan; Bambang Dwirahardjo (DiscoverSys Inc., 2021)
Objective: To determine the effect of Low Intensity Pulse Ultrasound (LIPUS) on the neutrophil function and epithelial thickness after skin excision in diabetes mellitus type 2 rats’ model (an Immunohistochemistry Study on Matrix Metalloproteinase-9).Material and Methods: Thirty-six Sprague dawley rats were divided into six groups: DM2, DM4, DM7, DML2, DML4, and DML7, each of which consist of 6 rats. Rats that matched the inclusion criteria were made into diabetes mellitus type 2 by injecting Nicotinamide and Streptozotocin. In all rat’s excision wound was made with punch biopsy in the back area. DML group received LIPUS therapy in the wound area (frequency: 3 MHz, intensity: 0.5 W/cm2, duty cycle: 20%, duration: 3 minutes every day) for two days (DML2), four days (DML4) and seven days (DML7). In the wound tissue an immunohistochemical examination was performed with Polyclonal Antibody MMP-9 to observe MMP-9 expression and and Periodic Acid-Schiff staining to observe epithelial thickness.Results: Two-Way ANOVA and Post-Hoc LSD test showed lower level of MMP-9 expressions in the DML group than in the DM group, whereas the epithelial thickness in the DML group was found higher than in the DM group. The Pearson test showed a correlation between the level of MMP-9 expressions and epithelial thickness (p=0.000; r=-0.785).Conclusion: LIPUS therapy reduced MMP-9 expression and increases epithelial thickness.